PENYELESAIAN WANPRESTASI SEWA MENYEWA TANAH DENGAN SISTEM PEMBAYARAN PANEN PADI - Arfah, Arfah; Payung, Otniel (Jurnal Delik ADPERTISI, 2025)
Basically, a lease agreement is a common agreement, where each party involved in the agreement (hak fasakh), because the lease is a reciprocal agreement (exchange). The existence of a lease agreement certainly has legal consequences between the tenant and the landowner which gives rise to rights and obligations that must be fulfilled. If done properly and legally justified, it is called a performance. If a problem arises in an agreement/agreement, it is called a breach of contract. This study aims to determine the resolution of land lease defaults with a harvest payment system in Mattirotasi Village, Maros Baru District. This type of research is field research. While the nature of the research is descriptive. The data sources used are primary and secondary data sources. Data collection was carried out using interview techniques and documentation. The data findings are described descriptively and analyzed using inductive thinking. The results of this study indicate that the resolution of land lease defaults with a harvest payment system in Mattirotasi Village, Maros Baru District was carried out by means of peace through deliberation or by means of family that directly involved both parties only. Peace is a principle in Islam. Settlement of default through peace will be able to create a better sense of mutual understanding between the disputing parties because they themselves decide.